Extraction of Timber’s Features using GLCM, Color Moment and Isotropic Undecimated Wavelet Transform (IUWT) - Putri Nur Rahayu; Danang - Erwanto; Asti Riani Putri (JAREE (Journal on Advanced Research in Electrical Engineering), 2022)
Feature extraction can be used to know the characteristic of timber’s texture. Characteristic of timber’s texture can be used to help researcher to identify DNA of timbers which can be detected illegal logging in Indonesia. In this reseach the proposed method is combination GLCM, Color Moment, and Isotropic Undecimated Wavelet Transform (IUWT). The result of the proposed method has agood accuracy.